Water productivity in South Asia: spatial and temporal variations - Amarasinghe, Upali; Sikka, Alok; Perera, Madhusha; Alahacoon, Niranga (Springer, 2025)
This chapter assesses the variations and options for improving water productivity to address water risks and insecurity in South Asian countries. The water productivity indicators of focus are physical water productivity (PWP)—the production per unit of water use, and economic water productivity (EWP), the value of production per unit of water use. A significant potential exists to increase PWP in many South Asian countries and regions with no water scarcity. These regions require increased access to water. However, increasing EWP should take precedence under water-scarce conditions. The latter may require reducing water-intensive crop areas and diversifying to less water-intensive crops.